Sosialisasi Bioteknologi Konvensional bagi Siswa Sekolah Menengah Atas Negeri Kapan, Kabupaten Timor Tengah Selatan, Propinsi Nusa Tenggara Timur - Ni Putu Yuni Astriani Dewi; Maria Yasintha Moi; Muhammad Fajar Farid Amrulloh; Yunawati Sele; Maria Paulin Saridewi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity is an outreach about the initial introduction and use of local food ingredients to make new products through conventional biotechnology. This service activity was carried out at Senior High School of Kapan, South Central Timor Regency, with the main target being students in grades 10 to 12. The method used in this socialization was to present and demonstrate the results of making and how to make yogurt. To find out students' responses to this socialization, students write down their impressions and responses using a prepared questionnaire. The results of the socialization showed that SMAN Kapan students had very good enthusiasm in listening and asking and answering questions in the socialization. This is proven by the results of a questionnaire from 30 respondents who stated that they had good motivation and were interested in learning to process local food ingredients into conventional biotechnology products